DIAGNOSTIC AND CONTROL MEASURES TO TACKLE THE EMERGENCE OF THE NIPHA VIRUS IN PAKISTAN FROM ONE HEALTH PERSPECTIVE - SUBHAN , A; IJAZ , S; FAIZ , S; KHAN , MS; KHOSA , SA; KHAN , R; RIZVI , SBH; ZAFAR , MB; SOHAIL , M (Biological and Clinical Sciences Research Journal, 2023)
The emergence of the Nipah virus (NiV) presents a significant global health concern due to its potential for severe outbreaks and high fatality rates. The study’s primary aim was to find the diagnostic and control measures to tackle the emergence of the nipa virus in Pakistan from one health perspective. This cross-sectional study was conducted in Lahore from August 2023 to November 2023. The study utilizes multidisciplinary collaboration, encompassing human health, veterinary sciences, environmental sciences, and public health experts, ensuring a holistic evaluation of the situation. Data was collected from different regions of Pakistan. The study encompassed 500 suspected cases, ultimately confirming 80 cases of Nipah virus. Geographically, the North region exhibited a higher incidence, with 35 confirmed cases, while the South region reported 20 confirmed cases. Among age groups, individuals aged 25-45 accounted for 45 confirmed cases, followed by 46-65 years with 25 confirmed cases. It is concluded that Effective control measures were observed in certain aspects, such as surveillance systems’ ability to pinpoint clusters. Still, gaps in intersectoral collaboration and environmental involvement were evident, demanding immediate attention to fortifying these strategies.